Unraveling Adolescent Language & Reading Comprehension: The Monster's Data. (4th July 2022) - Goodwin, Amanda P.; Petscher, Yaacov; Reynolds, Dan
ABSTRACT: Purpose: This study explores the roles of morphological skills (Morphological Awareness, Morphological-Syntactic-Knowledge, Morphological-Semantic-Knowledge, and Morphological-Orthographic/Phonological-Knowledge), vocabulary (knowledge of definitions, relationships between words, and polysemous meanings), and syntax in contributing to adolescent reading comprehension. Specifically, we identify the relative importance of these language skills. Methods: A racially diverse sample of 1, 027 students grades 5 to 8 were studied. Dominance Analysis was used, which allows a rank ordering of the contribution of predictors. Results: Results suggest unique roles for each language area with particularly important roles for vocabulary and morphological awareness. Considering just morphology, four morphology skills each explained meaningful variance (13-17%) in reading comprehension, together explaining half the variance in standardized reading comprehension. Considering each language area, vocabulary, the four morphology skills, and syntax were shown to each explain meaningful variance, ranging from 9-13%, together explaining 62.9% of the variance in reading comprehension. Conclusions: Findings are interpreted within the Reading Systems framework. Findings confirm the role of vocabulary, morphology, and syntax in supporting reading comprehension and suggest a relatively stronger role for vocabulary and morphological awareness. The meaningful role of the four morphological skills also suggests a broad role for morphology. Implications for theory, research, and practice are shared.